Chronic Poverty
XVI, 307 p.
Keywords: Based on a decade of research by the Chronic Poverty Research Centre, this volume includes material on inter-generational transmission, the importance of assets and vulnerability, and conflict, and new thinking about the close relationship between social exclusion and adverse incorporation.